Between Inhale and Exhale: Yoga as an Intervention in Smoking Cessation. (April 2014) - Dai, Chia-Liang; Sharma, Manoj
The current study provided a review of evidence-based yoga interventions' impact on smoking cessation. The researchers reviewed articles obtained from MEDLINE (PubMed), EBSCOHOST, PROQUEST, MEDINDIA, CINAHL, Alt HealthWatch, and AMED databases. Inclusion criteria were as follows: ( a ) study published between 2004 and 2013, ( b ) study published in English language, ( c ) study used yoga-based interventions, ( d ) study involved smokers with varying level of smoking, ( e ) study used any quantitative design, and ( f ) study had physiological and/or psychological outcomes. A total of 10 studies met the inclusion criteria. Designs were 2 pre–post tests and 8 randomized controlled trials. Majority of the interventions were able to enhance quitting smoking rates in the participants under study. Yoga-based interventions hold promise for smoking cessation. Some of the limitations include short follow-up measurements and short duration of intervention.